2022
DOI: 10.1155/2022/3515101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Lysophosphatidylcholine on Growth Performance and Lipid Metabolism of Juvenile Turbot

Abstract: A 56-day feeding trial was conducted in a flow-through seawater system to investigate the effects of lysophosphatidylcholine (LPC) on growth performance and lipid metabolism of turbot. Four experimental diets were prepared, differing only in the LPC supplementation, namely, 0 (LPC-0, control), 0.1 (LPC-0.1), 0.25 (LPC-0.25), and 0.5% (LPC-0.5) of dry matter. Each diet was randomly fed to triplicate tanks. LPC-0.1 and LPC-0.25 led to significantly higher weight gain than the control diet, and the highest weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…The diets with 0.1–0.5% LPC also significantly enhanced the abundance of Romboutsia , which is characterized by producing bile salt hydrolase, synthesizing amino acids and vitamins, and utilizing simple carbohydrates [ 66 ]. The present results that higher proportions of digestive enzyme-producing bacteria were found in the LPC-supplemented groups were consistent with the previous results which showed that dietary LPC could significantly improve lipid digestion in turbot [ 28 ]. Interestingly, Clostridium perfringens , a type of diacylglycerol (DAG)-producing bacteria, was also evidently increased in the LPC groups.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The diets with 0.1–0.5% LPC also significantly enhanced the abundance of Romboutsia , which is characterized by producing bile salt hydrolase, synthesizing amino acids and vitamins, and utilizing simple carbohydrates [ 66 ]. The present results that higher proportions of digestive enzyme-producing bacteria were found in the LPC-supplemented groups were consistent with the previous results which showed that dietary LPC could significantly improve lipid digestion in turbot [ 28 ]. Interestingly, Clostridium perfringens , a type of diacylglycerol (DAG)-producing bacteria, was also evidently increased in the LPC groups.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to the LPC0 group, the weight gain in groups LPC0.1 and LPC0.25 was significantly higher ( p < 0.05), with the highest value observed in the LPC0.1 group and an intermediate value observed in the LPC0.5 group. As the growth performance was not the focus of this study, the detailed growth data has been published elsewhere [ 28 ], and thus not described and discussed in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatty acids (FA), and essential fatty acids (EFA) in particular, are useful indicators of both food quality and the nutritional condition of a fish (Tocher 2003). EFAs are not synthesised de novo by vertebrates in sufficient quantities to meet their physiological demands (Xu et al 2018).…”
Section: Introductionmentioning
confidence: 99%